Ingestão proteica na encefalopatia hepática: panorama atual - Augusti, Laís [UNESP]; Romeiro, Fernando Gomes [UNESP]; Franzoni, Letícia de Campos [UNESP]; Santos, Lívia Alves Amaral [UNESP]; Dorna, Mariana de Souza [UNESP]; Caramori, Carlos Antonio [UNESP] (My University, 2014)
Hepatic encephalopathy is a severe complication of cirrhosis and comprises a complex and multifactorial pathophysiology. However, ammonia exchange between different tissues still deserves attention in relation to neurological alterations. Hepatic encephalopathy treatment remains focused on the trigger factor correction and the ammonia formation. Therefore, it was believed that high-proteic diets could lead to hepatic encephalopathy through the accumulation of nitrogen compounds in the gastrointestinal tract, which could increase production and absorption of ammonia. Currently, it is known that proteic restriction is harmful to cirrhotic patients, but it is still utilized. Malnutrition is highly prevalent among cirrhotic individuals with hepatic encephalopathy, thus indicating a nutritional risk which is clearly related to higher mortality rates. Furthermore, there is an increase in the protein needs of these patients and also a relationship between the loss of lean mass and hyperammonaemia. For these and other factors herein discussed, today’s global guidelines recommend the ingestion of higher protein levels for patients with hepatic encephalopathy.

A encefalopatia hepática é uma complicação grave da cirrose e envolve uma fisiopatologia complexa e multifatorial. Entretanto, a influência da amônia nos diferentes tecidos ainda merece atenção no que se refere às manifestações neuropatológicas. O tratamento da encefalopatia hepática permanece focado na correção do distúrbio desencadeante e na diminuição da formação da amônia a partir do cólon. Por conta disso, acreditava-se que dietas ricas em proteínas poderiam desencadear a encefalopatia hepática por meio do aporte de nitrogênio no trato gastrointestinal, podendo aumentar a produção e a absorção da amônia. Atualmente, sabe-se que a restrição proteica é prejudicial para portadores de cirrose, embora ainda utilizada. A desnutrição é prevalente entre indivíduos cirróticos com encefalopatia hepática, indicando um estado nutricional de risco que está nitidamente relacionado às maiores taxas de mortalidade. Além disso, há um aumento nas necessidades proteicas desses pacientes e uma relação entre a perda de massa magra e a hiperamoniemia. Com base em tais fatores, os guidelines atuais mundiais recomendam dieta hiperproteica para pacientes com encefalopatia hepática.
Protein intake in hepatic encephalopathy: current concepts
Keywords: Hepatic encephalopathy; Dietary proteins; Liver cirrhosis; Malnutrition|Nutrition therapy; Encefalopatia hepática; Proteínas; Cirrose hepática; Desnutrição; Terapia nutricional